The Relationship Between Human Papillomavirus and Epstein-Barr Virus Infections in Relation to Age Of Patients With Cervical Adenocarcinoma - Hei-Yu Lau; Nae-Fang Twu; Paul Chih-Hsueh Chen; Chiung-Ru Lai; Chi-Mou Juang; Ming-Shyen Yen; Kuan-Chong Chao (Elsevier, 2009)
Objective: To examine the relationship between human papillomavirus (HPV) and Epstein-Barr virus (EBV) infections in relation to age of patients with cervical adenocarcinoma. Materials and Methods: Thirty samples of human cervical adenocarcinoma tissue were collected from the surgical pathology archive at Taipei Veterans General Hospital from 1996 to 2008. All samples were examined for EBV, HPV-16 and HPV-18 E6 DNA by conventional and real-time quantitative polymerase chain reaction assays. Results: HPV-16 DNA was detected in 10 cases (33.3%), HPV-18 DNA in 12 cases (40%), and EBV DNA in three cases (10%); there were negative findings in seven cases (23.3%). EBV combined with HPV-16 or HPV-18 was also detected in one case each. No link could be demonstrated between HPV and EBV in endocervical lesions. When 20 patients £ 45 years old were compared with 10 patients > 45 years old, HPV-18 E6 DNA was detected in 45% vs. 30% (9/20 vs. 3/10), HPV-16 E6 DNA in 40% vs. 20% (8/20 vs. 2/10), EBV DNA in 10% vs. 10% (2/20 vs. 1/10), and no virus DNA was detected in 10% vs. 50% (2/20 vs. 5/10). HPV and EBV were significantly more common in younger women (p < 0.001). Conclusion: HPV-18 plays a major role in adenocarcinomas at any age. A high prevalence of HPV DNA is significantly associated with cervical adenocarcinoma, especially in younger women. The results do not support a role for EBV in cervical adenocarcinogenesis or any relationship between EBV and HPV infection in adenocarcinoma.